Suicidal ideation and suicide attempts in children and adolescents with bipolar disorder: a systematic review of prevalence and incidence rates, correlates, and targeted interventions. (5th July 2013) - Hauser, Marta; Galling, Britta; Correll, Christoph U
Abstract : Objective: Pediatric bipolar disorder (PBD) is associated with poor outcomes, including suicidal ideation (SI) and suicide attempt (SA). However, frequencies and risk factors of SI/SA and targeted intervention trials for SI/SA in PBD have not been reviewed systematically. Methods: We conducted a systematic PubMed review, searching for articles reporting on prevalences/incidences, correlates and intervention studies targeting SI/SA in PBD. Weighted means were calculated, followed by an exploratory meta‐regression of SI and SA correlates. Results: Fourteen studies (n = 1595), in which 52.1% of patients were male and the mean age was 14.4 years, reported data on SI/SA prevalence (N = 13, n = 1508) and/or correlates (N = 10, n = 1348) in PBD. Weighted mean prevalences were: past SI = 57.4%, past SA = 21.3%, current SI = 50.4%, and current SA = 25.5%; incidences (mean 42 months of follow‐up) were: SI = 14.6% and SA = 14.7%. Regarding significant correlates, SI (N = 3) was associated with a higher percentage of Caucasian race, narrow (as opposed to broad) PBD phenotype, younger age, and higher quality of life than SA . Significant correlates of SA (N = 10) included female sex, older age, earlier illness onset, more severe/episodic PBD, mixed episodes, comorbid disorders, past self‐injurious behavior/SI/SA, physical/sexual abuse, parental depression, family history of suicidality, and poor family functioning. Race, socioeconomic status, living situation, and life events were not clearly associated with SA. In a meta‐regression analysis, bipolar I disorder and comorbid attention‐deficit hyperactivity disorder were significantly associated with SA. Only one open label study targeting the reduction of SI/SA in PBD was identified. Conclusions: SI and SA are very common but under‐investigated in PBD. Exploration of predictors and protective factors is imperative for the establishment of effective preventive and intervention strategies, which are urgently needed.